2021
DOI: 10.1136/bjophthalmol-2020-318252
|View full text |Cite
|
Sign up to set email alerts
|

Differential associations between body mass index with diabetes and vision-threatening diabetic retinopathy in an adult Chinese population

Abstract: PurposeTo investigate the associations between body mass index (BMI) with diabetes mellitus (DM) and vision-threatening diabetic retinopathy (VTDR).MethodsThis was a longitudinal study which included DM-free participants aged ≥40 years from the Lingtou Eye Cohort Study at baseline (2008–2010). Physical and ocular examinations were performed at baseline and annual follow-ups under standardised protocol. Two 45° non-mydriatic colour digital retinal photographs were obtained for each eye at all study visits, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Hypertension would cause increased retinal blood flow and lead to retinal hyperperfusion, a critical source of injury in DR associated with shearing damage to capillaries. The effect of elevated BMI on DR might be through irregulated blood viscosity, platelet function, oxidative stress and retinal inflammation[ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypertension would cause increased retinal blood flow and lead to retinal hyperperfusion, a critical source of injury in DR associated with shearing damage to capillaries. The effect of elevated BMI on DR might be through irregulated blood viscosity, platelet function, oxidative stress and retinal inflammation[ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 , 26 , 28 ]It is well known that dietary intake have a great impact on the risk of several chronic diseases, including DM and obesity [ 29 ]. Therefore, it is essential to investigate the potential correlation between food consumption and health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found a possible neutral association between BMI and DR, indicating the existence of both protective and adverse effects ( 25 ). Han and X’s study showed that a higher BMI increased the risk of developing diabetes but was not related to VTDR ( 26 ). However, a large-scale epidemiological study conducted in India in 2022 demonstrated no relationship between BMI and DR, but it did reveal a negative correlation between BMI and VTDR ( 11 ).…”
Section: Discussmentioning
confidence: 99%